Assessment of spinal cord abnormalities and its related factors in male students of Islamic Azad University at Semnan - Rashidi, M; Ghorbani, R (Advances in Nursing & Midwifery, 2010)
Background and aim Decreased mobility and physical activity are threatening factors of health and spinal cord as the basic axis of the body is of critical importance in this regard because any injury of deformity of it can cause body malfunction. The aim of this study was to assess abnormalities of spinal cord and some of their related factors in male students of Islamic Azad University at Semnan. Materials and methods In this descriptive study, 240 students in their Physical Education Course 1 took part in the study. New York Test Posture Screen validated and made reliable by content and test-retest (r=0.80) methods respectively as well as Matiyas Test were applied for the assessment. A 3-grade scale including good, fair and poor was used for classification and those classified as good were regarded normal and those classified as fair or poor were considered as abnormal. Data were analyzed by SPSS 14. Findings 91.3% of the subjects suffer at least from one of spinal cord abnormalities. The most common condition was falling shoulders (74.2%) and the least frequent was pelvic obliquity (2.5%). Matiyas test was negative in 58.8% (not able to remain in requested position). 33.3% was overweight and obese in terms of body mass index (BMI). Conclusion The results showed that the prevalence of spinal cord abnormalities in the subjects was very high (91.3%) mostly due to poor mobility, weakness in the muscles of upper extremities particularly those holding the spine and lack of exercise. Thus, planning for physical activities and exercise in the leisure time of students seems essential. Keywords: Spinal cord, Spinal cord abnormalities, Exercise, Scoliosis. *Corresponding Author: Mohammad Rashidi. Dept. of Physical Education, Islamic Azad University, Semnan, Iran. E-mail: Mrashidi48@Yahoo.com